The thermal structure of the anoxic trough in Lake Untersee, Antarctica. Issue 6 (19th November 2018) - Bevington, James; McKay, Christopher P.; Davila, Alfonso; Hawes, Ian; Tanabe, Yukiko; Andersen, Dale T.
Abstract: Lake Untersee is a perennially ice-covered Antarctic lake that consists of two basins. The deepest basin, next to the Anuchin Glacier is aerobic to its maximum depth of 160 m. The shallower basin has a maximum depth of 100 m, is anoxic below 80 m, and is shielded from convective currents. The thermal profile in the anoxic basin is unusual in that the water temperature below 50 m is constant at 4°C but rises to 5°C between 70 m and 80 m depth, then drops to 3.7°C at the bottom. Field measurements were used to conduct a thermal and stability analysis of the anoxic basin. The shape of the thermal maximum implies two discrete locations of energy input, one of 0.11 W m -2 at 71 m depth and one of 0.06 W m -2 at 80 m depth. Heat from microbial activity cannot account for the required amount of energy at either depth. Instead, absorption of solar radiation due to an increase in water opacity at these depths can account for the required energy input. Hence, while microbial metabolism is not an important source of heat, biomass increases opacity in the water column resulting in greater absorption of sunlight.